Automated and Efficient Monitoring System for Organic Waste Compost Processing based on The Internet of Things (IoT) - Sugiarto, Lilik; ady saputra, indrawan; Wariyanto Abdullah, Robi (BEST, 2026)
In developed countries, waste has been regarded as an important component of management systems as well as reuse practices. In contrast, developing countries, particularly Indonesia, still face various challenges in waste management. Approximately 60% of the total national waste generation originates from household waste, and about 39.98% of this amount has not been optimally managed. Processing organic waste into compost is an environmentally friendly alternative that can reduce waste volume while increasing the value of household and agricultural waste. However, conventional composting methods often encounter difficulties, especially in maintaining temperature and moisture stability, causing the decomposition process to be less optimal. Based on these issues, this study aims to design and implement an automated efficiency and monitoring system for compost processing based on the Internet of Things (IoT). The developed system utilizes an ESP32 microcontroller, a soil moisture sensor for moisture measurement, a DS18B20 sensor for compost temperature monitoring, as well as an automatically controlled water pump and a 12 V DC fan. Sensor data are transmitted in real time to the Blynk platform for remote monitoring purposes. The experimental results indicate that the system is capable of maintaining moisture levels within the ideal range of 50–60% and compost temperature within the optimal range of 30–40°C, enabling the composting process to operate more stably, efficiently, and in a controlled manner.